Sports Massage Training for Elementary School Physical Education Teachers - Agustiyanta; Manshuralhudlori; Rumi Iqbal Doewes; Pomo Warih Adi; Satria Yudi Gontara; Singgih Hendarto; Ahmad Septiandika Adirahma (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The school environment is a contributing factor to more than one-third (39.7%) of injuries that occur in schools. When an injury occurs, Physical Education (PE) teachers are the first individuals to provide assistance. This devotion aims to provide sports massage training for PE teachers so that they can manage the risk of injury based on sports massage theory and skills. Partners in this devotion are 20 Elementary School PE teachers aged 38.75±13.23 years. The community devotion method uses a collaborative participatory approach. The implementation of the training involves the delivery of theory and practice. Data were collected through questionnaires to evaluate knowledge before and after the training, as well as direct observation to evaluate practical skills. The results showed that the training increased the knowledge of PE teachers about sports massage, especially in understanding specific benefits such as increased blood flow (+23.33% in “strongly agree”), flexibility (+41.52% in “strongly agree”), muscle fatigue (+28.89% in “strongly agree”), and relaxation effects (+55.56% in “strongly agree”). The positive perception of PE teachers also experienced a strengthening, as seen from increased confidence in the value and recommendation of sports massage to others, as well as an expanded understanding of the scope of sports massage applications for various age groups. In terms of practical skills, PE teachers demonstrated satisfactory mastery of basic techniques such as stroking (mean 3.06), shaking (mean 3.00), and tapotement (mean 3.05), although some other techniques require further learning (mean <3.00). Overall, this devotion succeeded in improving the knowledge and skills of sports massage of Elementary School PE teachers.